Ответы и объяснения

  • Участник Знаний
2013-07-18T08:58:28+04:00
3/а+(а-3)/(а+5)=(3а+15+а^2-3а)/(а(а+5))=(15+а^2)/(а^2+5а)
2)2х^2/(х^2-4)-2х/(х+2)=(2х^2-2х(х-2))/(х^2-4)=(2х^2-2х^2+4х)/(х^2-4)=4х/(х^2-4);
3)7а/(а-b)-7=(7a-7(a-b))/(a-b)=(7a-7a+7b)/(a-b)=7b/(a-b)
Лучший Ответ!
  • AlbuRin
  • светило науки
2013-07-18T08:59:26+04:00
1)  3/a + (a-3)/(a + 5) = (3*(a  + 5) + a(a - 3)) /a (a + 5) = (3a + 15 +a^2 - 3a)/a(a + 5) =
     =(a^2 + 15)/a(a + 5)
2)  (2x^2)/(x^2 - 4) - 2x/(x + 2) = (2x^2 - 2x(x - 2))/(x^2 - 4) =
     = (2x^2 - 2x^2 + 4x)/(x^ - 4) = 4x/(x^2 - 4)
3)  7a/(a - b) - 7 = (7a - 7(a - b))/(a - b) = (7a - 7a + 7b)/(a - b) = 7b/(a - b)